Cavin3 Suppresses Breast Cancer Metastasis via Inhibiting AKT Pathway - Xin An; Xin An; Xin An; Xi Lin; Xi Lin; Anli Yang; Anli Yang; Qiwei Jiang; Bingchuan Geng; Mayan Huang; Mayan Huang; Jiabin Lu; et al. (Frontiers in Pharmacology, 2020)
ObjectiveCavin3 is a putative tumor suppressor protein. However, its molecular action on tumor regulation is largely unknown. The aim of the current study is to explore the implication of cavin3 alteration, its clinical significance, and any potential molecular mechanisms in the regulation of breast cancer (BC).MethodsTCGA (The Cancer Genome Atlas) and GTEx (Genotype-Tissue Expression) data bases, and 17 freshly paired BC and adjacent normal tissues were analyzed for mRNA levels of Cavin3. Furthermore, cavin3 protein expression from 407 primary BC samples were assessed by immunohistochemistry (IHC) and measured by H-score. The clinical significance of cavin3 expression was explored by Kaplan-Meier analysis and the Cox regression method. In vitro biological assays were performed to elucidate the function and underlying mechanisms of cavin 3 in BC cell lines.ResultsCavin3 mRNA was dramatically down-regulated in BC compared with the negative control. The median H-score of cavin3 protein by IHC was 50 (range 0-270). There were 232 (57%) and 175 (43%) cases scored as low (H-score≤50) and high (H-score >50) levels of cavin3, respectively. Low cavin3 was correlated with a higher T and N stage, and worse distant metastasis-free survival (DMFS) and overall survival (OS). Multivariate survival analysis revealed low cavin3 was an independent fact for worse DMFS. In BC cells, an overexpression of cavin3 could inhibit cell migration and invasion, and significantly decreased the level of p-Akt. Knockout of cavin3, meanwhile, promoted cell invasion ability and increased the level of p-AKT.ConclusionCavin3 expression is significantly lower in BC and is correlated with distant metastasis and worse survival. Cavin3 functions as a metastasis suppressor via inhibiting the AKT pathway, suggesting cavin3 as a potential prognostic biomarker and a target for BC treatment.